MENGEMBANGKAN STRATEGI PROMOSI PRODUK INFORMASI PERPUSTAKAAN BERBASIS VISUAL CONTENT - Dian Kristyanto (Ikatan Pustakawan Indonesia, 2018)
The internet and the habits of people who prefer watching and listening become one of the opportunities that can be used for promotion. The library has been using library services and facilities, while information products can be used to guide people who can find out the information presented in the print collection. The method used to provide information on the promotion of information products through a visual process. Develop visual content-based promotion strategies that require visualization that can be used as resources. In addition to building visual content there are several elements that need to be known by a librarian or visualiser, such as regulation, balance, color, legibility and interest.